Serum Free Light Chain Only Myeloma with Cytoplasmic IgM - Hideaki Ebana; Ken-ichi Nakamura; Yoshihiro Nozawa; Ritsuko Seki; Masayuki Mita (Case Reports in Hematology)
In the past decade, the serum free light chain (FLC) immunoassays have become widely available enabling greater sensitivity in the diagnosis and management of monoclonal light chain diseases. Here, we describe a rare case of serum free light chain only myeloma with cytoplasmic IgM. A 75-year-old woman presented with a progressively worsening lumbosacral pain. FDG PET/CT images showed increased FDG uptake in the sacral mass, vertebral bodies, and ribs. Laboratory data found hypogammaglobulinemia and the bone marrow aspirate revealed only 2.2% of plasma cells. The serum and urine protein electrophoresis did not detect a monoclonal band. However, the serum FLC immunoassays reported an abnormal kappa/lambda ratio (0.001) indicating the presence of monoclonal lambda FLC. The sacral tumor biopsy revealed proliferation of plasma cells and immunohistochemical staining showed that the plasma cells were positive for CD138, IgM, and lambda light chain but negative for CD20. This case may have previously been described as a nonsecretory IgM myeloma but recently would be identified as free light chain only myeloma. The immunohistochemical and genetic features of the clonal plasma cells in free light chain only myeloma need to be further investigated to better understand the relevance and incidence of this myeloma type.